Climate change adaptation policies in Bangladesh: gap analysis through a gender lens (BRAC University Journal, 2026)
Policy reform is a necessary approach to implementing appropriate responses to climate change. Despite the acceptance of the role of gender in determining vulnerabilities related climate change, low reorganization has been given to gender concerns in the climate change policy documents of Bangladesh. In this regard, gender sensitivity of the key national policies about climate change in Bangladesh was assessed The discussion also identified some of the existing gaps in the reviewed policy documents. Identified gaps include generalization of women, lack of operational planning to address the vulnerabilities women, lack of recognizing roles of women as active contributors to adaptation and mitigation strategies. It was found that policy objectives related to climate change aud gender are addressed in a mutually exclusive manner. Finally, this paper provided recommendations to address the gaps and making gender more central to all policy development.